PENGELOLAAN PROGRAM DESA MAJU INHIL JAYA (DMIJ) DI DESA SUNGAI TERITIP KECAMATAN KATEMAN - Fuji Irvani Syafisqi; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Desa Maju Inhil Jaya (DMIJ) program is a program of the Regent of Indragiri Hilir Regency. This program is a district government program through an empowerment approach by streamlining the functions of the village government, Village Institutions and Village Communities to plan, implement, preserve and supervise development in a participatory manner. Various problems occur in the Teritip River Kateman sub-district where there are still inadequate roads, so there is a need to follow up on infrastructure development through this Program.The concept used is the G.R Terry theory that there are 4 indicators regarding management functions: Planning, Organizing, Implementation, Supervision. This study uses qualitative research with a phenomenological approach and the data required both primary and secondary are obtained by observation, interview and documentation techniques. The results of this study indicate that the first is the management of the advanced village program Desa Maju inhil jaya (DMIJ) in Sungai Teritip Village, Kateman District, which has not been running optimally. Second, the factors that hinder the management of the advanced village program inhil jaya (DMIJ) in Sungai Teritip Village, Kateman District, namely: Human Resources, Coordination, Natural Conditions. Keywords: Management, Program.